Verbal and nonverbal communication (Herald of Journalism, 2020)
The article examines the guestion about verbal and nonverbal com- munication A. Zhumagulova of which is studied within the framework of general linguistics. Author reviews about the term «communication» in re- lation to a linguistic sphere, and tells about composition as the most dif-  ficult process of linguistic communication. The author explains such terms    as «verbal and nonverbal» communication «linguistic relation» and «non- linguistic contact», and describes their jeneral features and differences. The author also tells the role of language event and the implementor addressee, sender, channel, report and the in function.
Keywords: communication, linguistic contact, non-linguistic contact, news, individual, addresser.